Deposition of a nanocomposite (Ti, Al, Si)N coating with high thickness by high‐speed physical vapor deposition. Issue 3 (17th March 2020) - Bobzin, K.; Brögelmann, T.; Kalscheuer, C.; Yildirim, B.; Liang, T.
Abstract: Nanocomposite coatings such as (Ti, Al, Si)N have been demonstrated as promising candidates for the use as protection against solid particle erosion for compressor blades. Typically, nanocomposite (Ti, Al, Si)N coatings are deposited by different physical vapor deposition (PVD) techniques. However, the relatively low coating thickness up to a few micrometers due to low deposition rates leads to a limited lifetime of the coatings under erosive particle bombardment. In this study, the deposition of a nanocomposite (Ti, Al, Si)N coating was performed by a hollow cathode gas flow sputtering method, the high‐speed physical vapor deposition, which enables the high‐rate deposition of thick coatings. Morphology and microstructure of the coating were investigated via scanning electron microscopy and transmission electron microscopy, respectively. Tribological characterization by impact tests and erosion tests demonstrates that the nanocomposite (Ti, Al, Si)N coated sample reveals a promising resistance against impact loads and the solid particle erosion. Summarily, nanocomposite (Ti, Al, Si)N coatings deposited by the high‐speed physical vapor deposition provide a high potential for the erosion protection of compressor blades. Translation abstract: Nanokomposit‐Beschichtungen wie (Ti, Al, Si)N haben sich als vielversprechende Kandidaten für den Schutz von Kompressorlaufschaufeln vor Festkörperpartikelerosionen erwiesen. Typischerweise werden Nanokomposit‐(Ti, Al, Si)N‐Beschichtungen mittels Physical Vapour Deposition hergestellt. Jedoch führt die relativ geringe Dicke dieser Beschichtungen von einigen Mikrometern aufgrund der niedrigen Abscheideraten zu einer begrenzten Dauer der Schutzwirkung vor erosiven Beanspruchungen. In dieser Studie wurde eine Nanokomposit‐(Ti, Al, Si)N‐Beschichtung mit einem Hohlkathoden‐Gasfluss‐Sputterverfahren, der High‐Speed Physical Vapour Deposition, abgeschieden, welches die Herstellung von dicken Beschichtungen mit hohen Abscheideraten ermöglicht. Tribologische Charakterisierung durch Impact‐ und Erosionstests zeigt, dass die mit Nanokomposit‐(Ti, Al, Si)N beschichtete Probe eine vielversprechende Beständigkeit gegen schlagende Belastungen und Festkörperpartikelerosion aufweist. Die mittels Hochgeschwindigkeits‐PVD‐Beschichtung abgeschiedenen Nanokomposit‐(Ti, Al, Si)N‐Beschichtungen bieten damit ein hohes Potenzial für den Erosionsschutz von Kompressorlaufschaufeln.